CALCULATIONS OF POSITIONS AND RESIDUES OF REGGE-POLES - Sukumar, C; Bardsley, J (1975)
A variational principle for the position of Regge poles in potential scattering is derived and applied to two problems, one of which provides a model for elastic e-Ar scattering. Direct numerical techniques are applied to a potential representing p-Ar collisions and the results are compared to recent JWKB calculations.